THE EFFECT OF CAPITAL STRUCTURE, FREE CASH FLOW AND FIRM SIZE ON FIRM VALUE WITH ESG DISCLOSURE AS A MODERATING VARIABLE - Dwi Kartika; Reni Dwi Widyastuti; Febriati Febriati (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study will examine the influence of capital structure, free cash flow, and company size on company value during 2020–2024, with Environmental, Social, and Governance (ESG) disclosure as a moderating variable in industrial companies listed on the Indonesia Stock Exchange. The researchers analyzed the data using selective sampling and a quantitative approach known as Moderated Regression Analysis (MRA), which produced 187–188 conclusions. The findings demonstrate that while capital structure and firm size have a positive and significant impact on business value, free cash flow has a negative impact. Firm size, free cash flow, and firm value are all impacted by ESG disclosure, but the relationship between capital structure and firm value is unaffected. In general, ESG moderates business value selectively.